Perceptions of Fishing Vessel Owners Based at Ocean Fishing Poft of Nizam Zachman Jakarta Regarding the Implementation of Measurable Fisheries Policies - Cahyarani, Ardelia; Susanto, Adi; Hamzah, Asep (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Measured Fishing (PIT) is a policy that will be implemented with the main principle of controlling the number of fish caught to maintain the sustainability of fish resources. Implementation of PIT is carried out through restrictions (quotas) and determination of fishing zoning in fisheries management areas (WPP). This research aims to analyze the perceptions of fishermen who own boats with bouke ami fishing gear and drop nets regarding the implementation of PIT based at the Jakarta Nizam Zachman Ocean Fishing Port (PPSNZJ). Primary data was obtained from observations and interviews conducted in June 2023 with 32 respondents. Secondary data was obtained from various PPSNZJ statistical publications and relevant scientific publications. Data was analyzed descriptively. The results of the research show that the diversity of fishermen's perceptions regarding the implementation of measured fisheries policies can be well received by all parties involved, although there are some fishermen who are still not comfortable with the implementation of these policies but still adapt and follow the regulations set by PPS Nizam Zachman Jakarta.